Is The Blue Economy A Driver Of Fisheries Sector Growth In Java? - Dikky Nur Hidayat (Journal of Islamic Economics Perspectives, 2025)
The blue economy is one of the main strategies for promoting sustainable economic growth, particularly in maritime countries such as Indonesia. The potential for developing the blue economy in Indonesia, especially on the island of Java, is enormous, with the value of capture fisheries production showing a positive trend every year. However, when viewed from the contribution of the fisheries sector to GDP, it is still small compared to other sectors, accounting for around 2.54% of total national GDP in 2024. This study aims to analyze the impact of the blue economy, measured through production value, the number of fishing households and fishing companies (RTP-PP), and the realization of fisheries sector investments on the regional domestic product (GRDP) of six provinces (Banten, Jakarta Special Capital Region, West Java, Central Java, Yogyakarta Special Region, and East Java) on the island of Java.  The research method used is quantitative analysis with a multiple regression model using the common effect model (CEM) as the selected model in this study. The data used are sourced from the Central Statistics Agency (BPS) and the Ministry of Marine Affairs and Fisheries (KKP) for the period 2018–2022. The findings of this study indicate that the blue economy sector, specifically the value of fisheries production and RTP-PP, has a positive and significant impact on the GRDP of the six provinces on the island of Java from 2018 to 2022. However, the variable of actual investment in the fisheries sector has a less significant impact on the fisheries sector GRDP in Java. The results of this study indicate that increasing the fisheries production sector and the number of RTP-PP can serve as drivers in maximizing the economic benefits of the blue economy for the growth of the fisheries sector. Therefore, the government needs to optimize policies that encourage factors in the blue economy oriented toward sustainability and efficiency in the fisheries and marine sectors.